A low-cost towed video camera system for underwater surveys: comparative performance with standard methodology - Trobbiani, Gastón Andres (2018)
Technological advances in the field of underwater video have led to an exponential increase in the use of drifting cameras (DC) and remotely operated vehicles (ROVs) to monitor the diversity, abundance, and size structure of marine life. Main advantages of DCs relative to ROVs are their lower costs and the much simpler logistics required to operate them. This study compares the performance of a new low-cost DC system equipped with a novel measuring device with that of a standard DC bearing an array of laser pointers. The new DC, which can be operated from a small boat, carries a pair of parallel steel “whiskers” that are dragged on the seabed within the field of view of the camera, providing a scale for measuring and estimating the density of benthic biota. An experiment conducted using an array of objects of known sizes laid on the bottom showed that its performance in terms of both size and density estimation was similar to that of the standard technique based on laser pointers. Measurement errors had a negligible negative bias (− 2.3%) and a standard deviation that ranged between 13 and 8% for objects from 25 to 110 mm in size. The whiskers offered a simplified method for density estimation that avoids the need to calculate the width of the field of view, thus reducing the video processing time by around 60% with respect to the standard method. Briefly, the new system offers an efficient low-cost alternative for benthic ecology studies conducted on soft or non-irregular bottoms.